2020
DOI: 10.1186/s13059-020-1943-5
|View full text |Cite
|
Sign up to set email alerts
|

A rare codon-based translational program of cell proliferation

Abstract: Background The speed of translation elongation is primarily determined by the abundance of tRNAs. Thus, the codon usage influences the rate with which individual mRNAs are translated. As the nature of tRNA pools and modifications can vary across biological conditions, codon elongation rates may also vary, leading to fluctuations in the protein production from individual mRNAs. Although it has been observed that functionally related mRNAs exhibit similar codon usage, presumably to provide an eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 74 publications
4
58
0
Order By: Relevance
“…The method is based on the incorporation of L-HPG, an amino acid analog of methionine containing an alkyne moiety, and Alexa Fluor 594 azide. The seeding of MDA-MB-231 cells and incubation of HPG in the medium were performed exactly as done earlier in the laboratory (Guimaraes et al, 2020). HeLa cells, in a slight modification from MDA-MB-231 cells, were incubated with HPG for a 30-min duration as per manufacturer's protocol.…”
Section: Quantification Of Nascent Protein Synthesis By Hpg Assaymentioning
confidence: 99%
“…The method is based on the incorporation of L-HPG, an amino acid analog of methionine containing an alkyne moiety, and Alexa Fluor 594 azide. The seeding of MDA-MB-231 cells and incubation of HPG in the medium were performed exactly as done earlier in the laboratory (Guimaraes et al, 2020). HeLa cells, in a slight modification from MDA-MB-231 cells, were incubated with HPG for a 30-min duration as per manufacturer's protocol.…”
Section: Quantification Of Nascent Protein Synthesis By Hpg Assaymentioning
confidence: 99%
“…In some organisms, however, the correspondence between optimal codon use in highly expressed genes and the matching tRNA abundance has been weak [ 23 ], or not observed for some codons [ 91 , 92 ], which has been interpreted as limited/absent support for adaptation of tRNA abundance and optimal codon use in certain systems [ 23 , 92 ]. However, growing evidence suggests that there is a complex supply-demand relationship between codons and tRNAs that may affect multiple aspects of translation [ 45 47 , 93 ], such that a universal connection between optimal codons and matching tRNA gene copy numbers may not always be expected even under a selection model [ 20 , 45 , 47 ]. For instance, some optimal codons may obligately require wobble tRNAs (no direct matching tRNAs) [ 20 ], which act to allow slow translation [ 51 , 52 ], and thus a positive relationship between codon use in highly expressed genes and high tRNA abundance would not be expected for those codons.…”
Section: Resultsmentioning
confidence: 99%
“…The distinct transcript pools present in proliferation and differentiation have been shown to have opposing synonymous codon usage signatures (7678). mRNAs enriched for AU-ending codons are abundant in proliferation, whereas it is the mRNAs that contain more GC-ending codons that are abundant in differentiation (77,78). Having observed a clear distinction in how GC-ending and AU-ending codons impact Ccr4-Not-mediated regulation of an mRNA’s stability (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies in human cells have also found AU-ending codons to be destabilising (81,123), whereas another study has found GC-ending codons to be destabilising (94). It is of note that this differential regulation may change with cellular context as it has been demonstrated that mRNAs preferentially involved in proliferation (enriched for AU-ending codons) and differentiation (enriched for GC-ending codons) have distinct codon usage and the tRNA pool available is altered to reflect this (77,78,124). Thus, the inconsistency in whether it is the AU-ending or GC-ending synonymous codons that are classified as destabilising in the literature could be explained by conditional differences.…”
Section: Discussionmentioning
confidence: 99%